Prognostic significance of MDM2 gene expression in childhood neuroblastoma - Inomistova, M.V.; Svergun, N.M.; Khranovska, N.M.; Skachkova, O.V.; Gorbach, O.I.; Klymnyuk, G.I. (Experimental Oncology, 2015)
Aim: To investigate the association of MDM2 expression at the mRNA levels in neuroblastoma with clinical features and unfavorable disease factors to determine the possibility of it usage as a prognostic marker of neuroblastoma. Materials and Methods: Total RNA and DNA were extracted from tumor tissue samples of total 91 neuroblastoma patients (mean age: 39.45 ± 4.81 months). MDM2 mRNA levels were detected with Q-PCR. TP53 gene deletion was detected with FISH method. MYCN amplification was detected with Q-PCR analysis in fresh tumor samples and FISH in FFPE samples. Results: We investigated the association of MDM2 mRNA expression with clinical outcome in neuroblastoma patients (n = 91). Kaplan — Meier curves showed a significant association of high MDM2 expression with poor event-free survival (p < 0.001). Clinical outcome of patients without MYCN amplification with low MDM2 expression was associated with better event-free survival than with high MDM2 expression (p < 0.001). Overexpression of MDM2 can be used as significant prognostic marker for patient stratification on risk groups and treatment optimization. Conclusion: Our results showed that the high expression of MDM2 at mRNA levels is an important factor of neuroblastoma prognosis. It may be a valuable additional molecular marker in guiding specific therapy in MYCN non-amplified NB patients without TP53 gene deletion. Key Words: neuroblastoma, MDM2 mRNA expression, MYCN gene amplification, p53/MDM2 interaction.